Kebijakan Pemberian Bebas Visa Kunjungan Kepada Warga Negara Singapura dalam Skema Travel Bubble Indonesia Pasca Covid-19 - Rizkiyanti, Amanda Femalia; Zahidi, M. Syaprin (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2024)
Covid-19 has major impact on the Indonesian tourism sector which is the second-largest foreign exchange contributor in Indonesia. The decline of the tourists’ visit has affected several regions of tourist destinations in Indonesia and Batam is one of them. To restore the tourism sector and to revitalize the economic condition post Covid-19, Indonesia provides a travel bubble policy to Singapore as the partner country. The purpose of the study is to find out the implementation of the policy of visit visa exemption to Singapore in the Indonesian travel bubble cooperation scheme of the post Covid-19 economic recovery. The study is considered as one of the national interest concepts. This study used a qualitative descriptive research method. The study concludes that by implementing the visit visa exemption policy to Singaporean, the tourists visit to Batam has increased. It is also expected that this policy will improve bilateral relations between Indonesia and Singapore and strengthen the Indonesia economy post Covid-19.